Dendrobium ormerodii (Orchidaceae, Dendrobieae), a new Dendrobium species from Central Kalimantan, Indonesia - Naive, Mark Arcebal K.; Handoyo, Frankie; Champion, Jeffrey (Phytotaxa, 2021)
A species new to science, Dendrobium ormerodii Handoyo, Naive & J.Champ. from Kalimantan, Borneo is herein described and illustrated. The species is superficially similar to D. fulminicaule but differs in having shorter stem, narrower leaf, dorsal sepal with acute apex, labellum without sidelobes or without the broadening at the base, labellum apex obtuse-truncate, and shorter column. Detailed description, a colour plate, line drawing, notes on phenology, distribution, and a conservation assessment are provided below.